Effectiveness of Project Based Learning Models on Microsoft Office Integration Competencies at SMK Negeri 1 Cerme - Rohman, Kholilur; Ashab, Khoirul; Akbar, Kamilah Salsabila Sofatul; Safitri, Lailatul; Mahameru, Krisna Bayu; Amroin, Jaya Abadi; Harimurti, Rina; Ma’mun, Syukron (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model in improving learning outcomes, learning interest, and the implementation of learning syntax in the Microsoft Office integration competency at SMK Negeri 1 Cerme. The research employed a Classroom Action Research (CAR) method conducted in two cycles, involving 36 students from class X DKV 1. The results showed a significant improvement in students' cognitive, psychomotor, and learning interest aspects. Learning mastery increased from 13.89% (pretest) to 94.44% (posttest), with statistical tests confirming a significant difference (p=<0.001). Students' learning interest and the implementation of PjBL syntax also showed positive growth. The study concludes that PjBL is effective in optimizing Microsoft Office integration learning. It is recommended that teachers adopt PjBL by providing scaffolding, contextual projects, and visual time management tools to enhance skill-based learning in vocational schools.